Role of Hypocretin in the Medial Preoptic Area in the Regulation of Sleep, Maternal Behavior and Body Temperature of Lactating Rats. (1st November 2021) - Rivas, Mayda; Serantes, Diego; Peña, Florencia; González, Joaquín; Ferreira, Annabel; Torterolo, Pablo; Benedetto, Luciana
Highlights: HCRT-1 in mPOA of lactating rats increase wakefulness and body temperature. Dual orexin receptor antagonist (DORA) in mPOA increased slow wave sleep and REM sleep. DORA in mPOA of postpartum rats increased nursing and milk ejection. HCRT-1 and DORA in mPOA of lactating rats did not modify EEG power spectrum. DORA in mPOA did not alter body temperature in lactating rats. Abstract: Hypocretins (HCRT), also known as orexins, includes two neuroexcitatory peptides, HCRT-1 and HCRT-2 (orexin A y B, respectively), synthesized by neurons located in the postero-lateral hypothalamus, whose projections and receptors are widely distributed throughout the brain, including the medial preoptic area (mPOA). HCRT have been associated with a wide range of physiological functions including sleep-wake cycle, maternal behavior and body temperature, all regulated by the mPOA. Previously, we showed that HCRT in the mPOA facilitates certain active maternal behaviors, while the blockade of HCRT-R1 increases the time spent in nursing. As mother rats mainly sleep while they nurse, we hypothesize that HCRT in the mPOA of lactating rats reduce sleep and nursing, while intra-mPOA administration of a dual orexin receptor antagonist (DORA) would cause the opposite effect. Therefore, the aim of this study was to determine the role of HCRT within the mPOA, in the regulation and integration of the sleep-wake cycle, maternal behavior and body temperature of lactating rats. For that purpose, we assessed the sleep-wake states, maternal behavior and body temperature of lactating rats following microinjections of HCRT-1 (100 and 200 µM) and DORA (5 mM) into the mPOA. As expected, our data show that HCRT-1 in mPOA promote wakefulness and a slightly increase in body temperature, whereas DORA increases both NREM and REM sleep together with an increment of nursing and milk ejection. Taken together, our results strongly suggest that the endogenous reduction of HCRT within the mPOA contribute to the promotion of sleep, milk ejection and nursing behavior in lactating rats.